“Efecto de las fases lunares en el rendimiento del cultivo de la cebolla china, variedad roja chiclayana (allium fistulosum L.) bajo condiciones agroecológicas en la provincia de Lamas” - Sisti Carbajal, Juan Manuel (2016)
This research aims to evaluate and determine which of the four lunar phases influence the increase in performance and economic benefits of growing green onion (Allium fistulosum L.), under the ecological conditions in the district of Lamas Province Lamas. The research was conducted on the grounds of the Fundo 'The Pacific" owned by Mr. Jorge Luis Pelaez Rivera, politically located in the district and province of Lamas, San Martin department. The statistical design of randomized complete block (RCBD) with four replications and four treatments, with a total of 16 experimental units was used. The information gathered in the field was processed using SPSS 19 statistical software, which uses the P-value comparator of significant levels of confidence 0.05 0.01 differences and the analysis of variance (ANOVA) and multiple range test of Duncan P s 0.05. He studied treatments were: New Moon, sown on 03/05/11, First Quarter, littered the 10/05/11, sown Full Moon Full Moon 17/05/11 and 26/05/11 sown, was used a gap of 0.20 meters x 0.20 meters. The variables evaluated were: plant height (cm) neck diameter (cm), bulb diameter (cm), plant weight (g), crop yield kg ha-1 and the economic analysis. The results obtained indicate that plants grown in full moon was the most appropriate treatment which found that influences the performance boost getting 30,268.76 kg ha-1, which resulted in a benefit I cost 1. 78 and a net profit of S J. 13285. 14 new soles, respectively. Keywords: Effect, phases, moon, new, waxing, full, waning, yield economic benefits, Dose, fertilizer, micronutrients, ecotype, yield, economic benefit.